Effectiveness of Jingjin Therapy for Non-Specific Chronic Neck Pain with Extension Dysfunction: A Randomised Controlled Trial - Gong Z; Gao Y; Liu W; Li W; Wu X; Li J (Journal of Pain Research)
Zhichao Gong,1 Yinyan Gao,2 Wenqi Liu,2 Wu Li,3 Xinyin Wu,2 Jiangshan Li3 1Department of Acupuncture and Massage, The Second Affiliated Hospital of Hunan University of Chinese Medicine, Changsha, Hunan, 410005, People’s Republic of China; 2Department of Epidemiology and Biostatistics, Xiangya School of Public Health, Central South University, Changsha, Hunan, 410013, People’s Republic of China; 3College of Acupuncture, Massage and Rehabilitation, Hunan University of Chinese Medicine, Changsha, Hunan, 410208, People’s Republic of ChinaCorrespondence: Xinyin Wu, Department of Epidemiology and Health Statistics, Xiangya School of Public Health, Central South University, No. 168-2, Tongzipo Road, Yuelu District, Changsha, Hunan, 410000, People’s Republic of China, Tel +86-18390825035, Email irenexywu@csu.edu.cn Jiangshan Li, College of Acupuncture, Tuina and Rehabilitation, Hunan University of Chinese Medicine, No. 300, Xueshi Road, Yuelu District, Changsha, Hunan Province, 410208, People’s Republic of China, Tel +86 13707315642, Email 001316@hnucm.edu.cnPurpose: To evaluate whether Jingjin therapy, a distal manual intervention, could accelerate extension dysfunction for non-specific chronic neck pain (NCNP).Patients and Methods: In this single-centre, two-arm randomised controlled trial, we enrolled Chinese patients aged 20– 60 years with active neck extension disorder, regardless of prior exposure to manual therapy. We randomly assigned 160 patients to one of the following two arms: Jingjin therapy or general manual therapy. Both groups underwent six treatment sessions: the first three sessions were administered daily, and the last three sessions were administered every other day. The primary outcome was the between-group difference in the angle of active neck extension after the sixth treatment and 1 week after treatment. A repeated-measures linear mixed-effects model was used to assess between-group differences in outcome indices, with group allocation and treatment time points treated as fixed effects and participants as random effects.Results: The change in the angle of active neck extension from baseline to the sixth treatment session was significant for Jingjin therapy (mean: 29.75° to 51.97°) and general manual therapy (mean: 28.18° to 52.49°). Further, the between-group difference was minimal (mean − 0.26°, 95% confidence interval, − 2.62°, 2.09°) and not statistically significant (P = 0.828).Conclusion: Jingjin therapy for 9 days significantly improved neck extension function in patients with NCNP, with no significant difference compared to general manual therapy.Clinical Trial Registry Id: ChiCTR2300068892.Plain Language Summary: This study evaluated the efficacy of Jingjin therapy, a massage technique employed for the treatment of non-specific chronic neck pain, in comparison with conventional manual therapy in adult populations. The primary objective was to assess whether Jingjin therapy could enhance neck mobility. The findings revealed that both therapeutic modalities were beneficial and exhibited comparable effectiveness. Notably, Jingjin therapy, characterized by its distal intervention site, demonstrated fewer side effects and was more readily accepted by patients. Consequently, Jingjin therapy may represent a viable alternative for the management of chronic neck pain. However, further research is warranted to determine its potential for use in conjunction with other treatment modalities and its efficacy in addressing other types of neck pain.Keywords: Jingjin, manual therapy, chronic neck pain, neck extension